2022
DOI: 10.3390/f13111966
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Environmental Factors on Short-Term Eye Strain Relief during COVID-19 Quarantine: A Pilot Study

Abstract: Some policies implemented during the pandemic extended the time that students spend on electronic devices, increasing the risk of physical and eye strain. However, the role of different environments on eye strain recovery has not been determined. We recruited 20 undergraduate students (10 males and 10 females) from a university in eastern China and explored the restoration effects of their eye strain in different types of spaces (wayside greenspace, a playground, a square, and woodland) on campus through scale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 78 publications
0
1
1
Order By: Relevance
“…The demographic section of the results also declared a significant impact of areas (urban/rural) towards the preference to use anti-glare coating. The finding contrasts with past literature that shows the adoption of such innovative solutions more strongly in urban populations [28][29][30][31].…”
Section: Regression Analysiscontrasting
confidence: 99%
“…The demographic section of the results also declared a significant impact of areas (urban/rural) towards the preference to use anti-glare coating. The finding contrasts with past literature that shows the adoption of such innovative solutions more strongly in urban populations [28][29][30][31].…”
Section: Regression Analysiscontrasting
confidence: 99%
“… 20 , 21 For eye health, green spaces have been associated with decreased eye strain and decreased refractive error. Lu et al 22 found that exposure to green space for 10 minutes improved eye strain among university students using a 15-minute eye strain stimulus task (post-stimulation eye strain level of 8.20 ± 8.15 vs. post-relax eye strain level of 5.85 ± 6.45; P < 0.001). Huang et al 23 found that a higher neighborhood greenness level decreased the odds of having astigmatism in preschoolers’ by 45% (aOR = 0.55; 95% CI, 0.43–0.70; P < 0.001) and myopia by 38% (aOR = 0.62; 95% CI, 0.38–0.99; P < 0.05) after adjusting for the child's age and gender, parental education, monthly household income, and parental vision status.…”
Section: Neighborhood and Built Environment Srfsmentioning
confidence: 99%